Tips for easy Excel - Abdul Ghani, Roseziahazni; Abu Samah, A’tiqah Rashidah; Mohamad, Zuraida; Yusuf Ali, Noorhayati (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2024)
Microsoft Excel software is one of the most crucial Microsoft Office products when it comes to data preparation. For those of you whose work involves data, this article will serve as an easy-to-learn Excel learning guide. Excel could be mastered quickly and easily. In this first series, let’s explore the many Excel shortcuts that can improve our productivity when we are using the spreadsheet.